2020
DOI: 10.1136/jitc-2020-001157
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against RhoC induces long-lasting immune responses in patients with prostate cancer: results from a phase I/II clinical trial

Abstract: BackgroundPeptide-based vaccination is a rational option for immunotherapy of prostate cancer. In this first-in-man phase I/II study, we assessed the safety, tolerability and immunological impact of a synthetic long peptide vaccine targeting Ras homolog gene family member C (RhoC) in patients with prostate cancer. RhoC is a small GTPase overexpressed in advanced solid cancers, metastases and cancer stem cells.MethodsTwenty-two patients who had previously undergone radical prostatectomy received subcutaneous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 47 publications
3
23
0
1
Order By: Relevance
“…To date, different peptide vaccines have been evaluated in early phase 1/2 clinical trials, with some thoroughly promising initial results. For example, targeting Ras homolog gene family member C (RhoC) induced a potent and long-lasting T cell immunity in the majority of patients who had previously undergone radical prostatectomy (NCT03199872) [ 110 ]. Additionally, human telomerase reverse transcriptase (hTERT) peptide vaccine UV1 in combination with GM-CSF induced specific immune responses in the majority of mHNPC patients unselected for HLA type with tolerable adverse events [ 111 ].…”
Section: Immunotherapeutic Treatment Approachesmentioning
confidence: 99%
“…To date, different peptide vaccines have been evaluated in early phase 1/2 clinical trials, with some thoroughly promising initial results. For example, targeting Ras homolog gene family member C (RhoC) induced a potent and long-lasting T cell immunity in the majority of patients who had previously undergone radical prostatectomy (NCT03199872) [ 110 ]. Additionally, human telomerase reverse transcriptase (hTERT) peptide vaccine UV1 in combination with GM-CSF induced specific immune responses in the majority of mHNPC patients unselected for HLA type with tolerable adverse events [ 111 ].…”
Section: Immunotherapeutic Treatment Approachesmentioning
confidence: 99%
“…Meanwhile, CD4+ T cell activation has evolved as an essential goal of cancer vaccines, whereby two main strategies are used. The first relies on the use of synthetic peptides, either as a mixture of exact MHC-class I and -class II ligands [ 124 , 125 ], or (overlapping) synthetic long peptides (SLPs) [ 126 , 127 , 128 , 129 ]. The second approach uses nucleic acids (DNA or RNA) encoding for the relevant antigens or fragments thereof.…”
Section: Harnessing Cd4+ T Cells For Immunotherapymentioning
confidence: 99%
“…Although the best anticancer vaccination strategy has not yet been identified (e.g., the vaccine basis, adjuvants or injection scheme), a number of clinical studies have demonstrated that targeting CD4+ T cells is safe. In our experience, antivaccine CD4+ T cell responses are often stronger than CD8+ T cell responses and also last longer, even after vaccination completion [ 128 , 132 ].…”
Section: Harnessing Cd4+ T Cells For Immunotherapymentioning
confidence: 99%
“…The vaccination with T-cell receptor gamma chain alternate reading frame protein (TARP) and pulsed DCs induced specific immune responses and reduced PSA velocity in D0 PCa patients (NCT00908258) and is currently under evaluation as DCs vaccination in the phase II NCT02362451 study [61]. In a phase I/II trial (NCT03199872), a peptide vaccine against the Ras homolog gene family member C (RhoC) GTPase determined strong CD4+ responses in 18/21 patients after RP [62].…”
Section: Other Taas and Personalized Peptide Vaccination (Ppv)mentioning
confidence: 99%